2010
DOI: 10.1007/s11146-010-9271-2
|View full text |Cite
|
Sign up to set email alerts
|

Real Estate Ownership, Leasing Intensity, and Value: Do Stock Returns Reflect a Firm’s Real Estate Holdings?

Abstract: Little is known about the effects of real estate ownership and leasing on the stock return characteristics of public firms. In this study, we first examine the sensitivity of retail firm returns to a real estate factor over the period 1998-2008. The retail industry is chosen because of the significant use of real estate in a typical retail firm's production function. Consistent with our expectations, retail stocks exhibit positive real estate risk exposure, even after controlling for sensitivity to general mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Using a portfolio formation methodology, which I adopt in this study, that study finds that real estate increases firm risk, resulting in a positive relation with returns. Tuzel argues that the positive effect of real estate on firm risk stems from the operating inflexibility, low 7 A simpler approach to dealing with this endogeneity issue is to restrict the analysis to one industry , Yu and Liow 2009, Ling, Naranjo and Ryngaert 2012. However, it is difficult to make general statements about the relation between real estate and stock returns from these studies.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Using a portfolio formation methodology, which I adopt in this study, that study finds that real estate increases firm risk, resulting in a positive relation with returns. Tuzel argues that the positive effect of real estate on firm risk stems from the operating inflexibility, low 7 A simpler approach to dealing with this endogeneity issue is to restrict the analysis to one industry , Yu and Liow 2009, Ling, Naranjo and Ryngaert 2012. However, it is difficult to make general statements about the relation between real estate and stock returns from these studies.…”
Section: Related Literaturementioning
confidence: 99%
“…A simpler approach to dealing with this endogeneity issue is to restrict the analysis to one industry (Brounen and Eichholtz , Yu and Liow , Ling, Naranjo and Ryngaert ). However, it is difficult to make general statements about the relation between real estate and stock returns from these studies.…”
mentioning
confidence: 99%
“…In our next two comparative firm samples, we narrow our focus to firms with high potential debt capacity—retail firms and firms with high asset tangibility. Ling, Naranjo and Ryngaert () show that retail firms are real estate intensive and their stock returns reflect their real estate holdings. Retail firms are classified as SIC codes 5200–5999, yielding 4,774 firm‐year observations over our sample.…”
Section: Datamentioning
confidence: 99%
“…Firms have an option to either own or lease CRE. CRE held by public listed nonreal estate firms is significantly under‐valued by the markets dampening stock prices of firms holding large CRE assets (Deng and Gyourko , Liow , Brouner and Eichholtz , Brounen, Colliander and Eichholtz , Ling, Naranjo and Ryngaert ). However, some firms still hold substantial CRE because of economic, operational and strategic considerations (Liow and Nappi‐Choulet ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have shown that CRE ownership has negative impact on the performance of nonreal estate firms (Linnerman , Deng and Gyourko , Brounen and Eichholtz, ). Firms with intensive real estate holdings, either through direct ownership or capital leases, are exposed to greater systematic and real estate market risks (Tuzel , Ling, Naranjo and Ryngaert, ). The results were derived based on the premise that CRE ownership is an exogenous variable that explains variations in firms’ stock market performance controlling for heterogeneity among firms.…”
Section: Introductionmentioning
confidence: 99%